2013
DOI: 10.1534/g3.113.006817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Adaptive Divergence Between Migratory and Nonmigratory Ecotypes of a Salmonid Fish, Oncorhynchus mykiss

Abstract: Next-generation sequencing and the application of population genomic and association approaches have made it possible to detect selection and unravel the genetic basis to variable phenotypic traits. The use of these two approaches in parallel is especially attractive in nonmodel organisms that lack a sequenced and annotated genome, but only works well when population structure is not confounded with the phenotype of interest. Herein, we use population genomics in a nonmodel fish species, rainbow trout (Oncorhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 66 publications
(100 reference statements)
3
113
3
Order By: Relevance
“…Genome-wide association analysis suggested different genomic regions underlying different phenotypic components of the migratory phenotype (Hecht et al, 2012(Hecht et al, , 2013. Annotation of genome regions linked to significant SNPs indicated they were likely in regions associated with physiological processes important in migration (Hecht et al, 2013;Hale et al, 2013). The study identified a number of new loci associated with migratory traits and corroborated loci that had been identified in earlier QTL studies.…”
Section: Migrationsupporting
confidence: 73%
“…Genome-wide association analysis suggested different genomic regions underlying different phenotypic components of the migratory phenotype (Hecht et al, 2012(Hecht et al, , 2013. Annotation of genome regions linked to significant SNPs indicated they were likely in regions associated with physiological processes important in migration (Hecht et al, 2013;Hale et al, 2013). The study identified a number of new loci associated with migratory traits and corroborated loci that had been identified in earlier QTL studies.…”
Section: Migrationsupporting
confidence: 73%
“…A matrix of SNP variation in the variant call format (VCF) was produced with populations, using (1) a minimum percentage of 80% of genotyped individuals in a population to process a locus for that population, (2) a minimum number of six populations where a locus must be present to be processed ( i.e . a locus must be present in all samples), (3) a minimum minor allele frequency of 2% and (4), since only 10 individuals per population were considered (Table ), loci that were heterozygous at 90% were discarded in order to remove paralogous loci (Hale et al ., ). The loci passing these filters were exported in VCF.…”
Section: Methodsmentioning
confidence: 99%
“…Data from Ofu indicate that thermal tolerance is a polygenic trait, where a number of alleles of small effect across many different cellular pathways are responsible for elevated thermal tolerance of the HV pool corals Palumbi et al, 2014). Polygenic traits are a common feature of high gene flow species and occur widely in marine populations (Limborg et al, 2012;Hale et al, 2013;Pespeni et al, 2013;Laporte et al, 2015;Barney et al, 2017).…”
Section: The Genetic Architecture Of Thermal Tolerancementioning
confidence: 99%